The importance of physical activity and diet in the life of female students - Pawłowski, Rafał; Dutkiewicz, Robert; Winiarczyk, Tomasz (Medical Studies/Studia Medyczne, 2015)
Introduction : The lifestyle is known to be the most influential factor for maintaining a good health condition. Lack of physical activity and poor nutrition are two factors that suport each other in a negative way and result in an increasing number of obese people. Irregular nutrition is often closely related to irregular academic life. Aim of the research: The objective of this research is to find out how female students perceive health – how they understand and define it. Another objective is to determine whether nurses-to-be and psychiatrists-to-be perceive health differently than other students and whether their health-esteem is backed with their free-time physical activity and regular nutrition. It is crucial to find out what factors, according to the research, have the biggest influence on people’s health. Material and methods: The research involved 180 female students of full-time courses at the Jan Kochanowski University in Kielce: 98 female students of the Health Sciences Faculty and 82 female students of other faculties. The method of a diagnostic survey and a questionnaire were used in the research. Results : The female students perceived health as a quality, well-being, an absence of disease; and for female nursing students health was not only the absence of disease or disability but also biopsychosocial well-being. The most important factors that influence the health condition are physical activity and nutrition. A high evaluation does not correspond to taking care of one’s health. Fewer than 8% of the female students practised sport in their free time and ate regularly. More than a half neither did sport nor ate regularly (Pearson’s contingency coefficient C reaches a value of 0.1). Conclusions : The female nursing students, contrary to the female students of other faculties, perceive health in the same way as the World Health Organisation. Regardless of faculty, physical activity and regular nutrition are considered to be the most important factors influencing our well-being. A high health-esteem among the researched students is not backed with their healthy lifestyles.